2006
DOI: 10.1111/j.1547-5069.2006.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Pain Management in the United States

Abstract: Greater clarity and consistency are needed in the use of the terms race, ethnicity, and minority. Groups were treated as if they were homogeneous, and details were lacking about whether subgroups of different races or ethnicities had been studied. Although reported disparities in pain management were small, they were consistent. Further research is needed to examine differences within groups and to explain possible reasons for disparities across groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 39 publications
(56 reference statements)
4
59
1
Order By: Relevance
“…With respect to race alone, AfricanAmericans experienced a difference in 2-year KSSs when compared with other races: African-Americans had a lower (p = 0.001) average 2-year KSS (86. 8 (Table 5). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to race alone, AfricanAmericans experienced a difference in 2-year KSSs when compared with other races: African-Americans had a lower (p = 0.001) average 2-year KSS (86. 8 (Table 5). …”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggest differences in function between races after joint arthroplasty [8,11,19,33]. Others have reported differences in the experience of pain by patients and in the management of that pain [8,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors may influence these practices, including patients' attitudes, language barriers, heterogeneity of groups, and the medical costs involved [4]. A retrospective cohort study conducted in a hospital emergency department in Atlanta disclosed that only 57% of African American patients received adequate analgesia compared to 74% of White American patients (p = 0.01) [3].…”
Section: Introductionmentioning
confidence: 99%
“…One particular study showed that ethnicity indeed influenced patients' pain and analgesic prescriptions [4]. This post-operative pain study was conducted among women in Singapore who had undergone a lower uterine segment caesarean section procedure.…”
Section: Introductionmentioning
confidence: 99%